Rare Delayed Ifosfamide Encephalopathy: A Case Report of Chemotherapeutic Neurotoxicity - Ambika Menon; Chidiebele A. Enunwa; William L. Read; Kyle P. James (Case Reports in Oncology, 2024)
Introduction: Neurotoxicity is a well-documented side effect of ifosfamide chemotherapy. The presentation includes hallucinations, seizures, disorientation, coma, and death. Treatment with methylene blue can shorten the duration and severity of symptoms. Ifosfamide neurotoxicity almost always happens during or shortly after drug infusion and so is usually immediately recognized. Here, we describe a case of ifosfamide neurotoxicity with onset 14 days after treatment started. Case Presentation: A 25-year-old woman with round cell sarcoma of the jaw presented to the emergency department with 2 days of encephalopathy and bizarre behavior. Antipsychotic medications and benzodiazepines produced no benefit. After consultation, oncology recommended methylene blue, hypothesizing that her symptoms could be a rare presentation of delayed ifosfamide-induced neurotoxicity, 14 days after first administration. After 4 days of methylene blue infusion, her functioning returned to baseline. Conclusion: Delayed ifosfamide-related neurotoxicity is a rare side effect of this chemotherapeutic agent and should be considered in the workup of altered mental status, even if symptoms occur after the previously accepted 5-day standard. In such patients, delayed symptomology may require extended use of methylene blue as treatment.